Predictive Maintenance in Aviation using Artificial Intelligence - Patibandla, Kondala Rao (Journal of Artificial Intelligence General science (JAIGS) ISSN:3006-4023, 2024)
Predictive maintenance in aviation using artificial intelligence (AI) is transforming the way aircraft are maintained and operated. By analyzing data from various aircraft sensors, AI algorithms can predict potential failures before they happen, allowing for timely and efficient maintenance. This proactive approach reduces unplanned downtime, enhances safety, and lowers maintenance costs. The implementation of AI in predictive maintenance leverages technologies such as machine learning, data analytics, and the Internet of Things (IoT) to monitor and analyze the health of aircraft components continuously. This abstract provides a comprehensive overview of how AI-driven predictive maintenance works, its benefits, and its impact on the aviation industry, making it easier for anyone to understand its significance and potential.